(3QSGdI dEHf MHjHs - (3eMeO Hf MHjH Hf CejI Hf YeQh GdgGTej, HGdhdGA, CHh LYaQ GdHZOGOj, ef ehGdj Hfj GdYHGS,J (B245 (3g` s
(3ChdgG (B:s
(3bGd eMeO Hf MHjH(B: (3PcQ ef Cf HTQ Hf gQhf deG HYK YHOGdQMef Hf eNfa Edi GdCRGQbI ai ebGJdI Cgd GdchaI CdN s
(3BNQgG (B:s
(3gPG BNQ eG hLOJg HNW GdMSjf Hf Ydi Gdfehi , jbhd (B: (3gPG BNQ eG hLOJg HNW GdScQi , jbhd (B: (3gPG BNQ eG hLOJg ai cJGH GHf MHjH s
(3YdjgG bUGFO ef TYQ SQGbIs
(3efbhdI ef NW GHf GdCYQGHis
(3bQf GdfSN (B:s
(3GdbQf GdNGeSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B78 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B174s
Keywords: (3GdCOHs